Architectural Patterns for Petabyte-Scale Data Processing in ML Infrastructure - Srinivasa Sunil Chippada (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the architectural patterns essential for processing petabyte-scale data in modern machine learning infrastructure. The article explores the evolution from traditional on-premise clusters to cloud-native architectures, highlighting transformative approaches in distributed processing and resource optimization. It explores advanced techniques in data skew handling, state management, and processing consistency while presenting innovative solutions for workload management and cost optimization. The article delves into modern architectural patterns such as lake house design and polyglot persistence, examining their impact on processing efficiency and system reliability. Special attention is given to implementation considerations, including fault tolerance mechanisms and migration strategies from on-premise to cloud environments. The article provides practitioners with insights into architectural trade-offs and their implications for ML workloads, offering a framework for building robust, scalable infrastructure.